Genetic Algorithm-Based Web Scheduler Enhances Fairness in Duty Allocation: Aplikasi Penjadwalan Berbasis Algoritma Genetika untuk Meningkatkan Keadilan Distribusi Piket - Onibala, Rahellea Joiby; Kumajas, Sondy Campvid; Moningkey, Efraim Ronald Stefanus (Universitas Muhammadiyah Sidoarjo, 2026)
This study aims to design and build a website-based application for scheduling fire and rescue personnel on duty at the Minahasa Regency Fire Department by implementing genetic algorithms. The main problem encountered is the manual scheduling process, which causes imbalances in schedule distribution, delays in information, and difficulties in adjusting when personnel changes occur. The system was developed using the Rapid Application Development (RAD) method thorugh the stages of needs identification, design, implementation, and testing. Genetic algorithms are used as an optimization mehod to produce a fair, efficient, and conflict free schedule. The system also provides a permit submission mechanism and automatic notifications to support officer communication and coordination. The results of User Acceptance Testing (UAT) showed an average score of 4.5 (versy good category), indicating that the system is easy to use and meets operational needs. Thus, this application contributes to improving the efficiency, accuracy, and transparency of the on-duty scheduling process at the Minahasa Regency Fire Department. HIGHLIGHTS • Ensures fair and conflict-free duty schedules using genetic algorithm optimization.• Improves communication and coordination with automated permit and notification features.• Achieves high usability with 4.5 UAT score, supporting operational readiness. KEYWORDS Genetic Algorithm; Scheduling System; Firefighters; Web-Based Application; Optimization